Implementation Devops Methods in Developing Church Asset Management Information Systems: A Software Engineering Approach for Efficiency and Quality - Manjaruni, Maryo Indra; Leunupun, Pieter; Tamtelahitu, Trientje Marlein; Nivaan, Goldy Valendria; Manaha, Roberth Ricky Y. (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research explores the use of the DevOps Method in developing a Church Asset Management Information System with a focus on efficiency and quality, taking into account the WebQual dimensions. DevOps methods are applied to improve software development, integration and management processes in order to achieve operational efficiency and improve software quality. The implementation of DevOps brings significant changes in the development life cycle, resulting in improvements in development cycle times and a decrease in software errors. Continuous Integration (CI) and Continuous Deployment (CD) practices are used to ensure fast and stable system updates. In addition, this research measures software quality by considering WebQual dimensions, such as sustainability, reliability, responsiveness, and security. Through analysis of test results and data collection, this research presents evidence that the application of DevOps methods not only increases development efficiency but also has a positive impact on software quality. These results are proven by improvements in user satisfaction, stakeholder engagement, and church meeting needs in their asset management